The Effect Of E-Service Quality, E-Promotion On Purchase Intentions Mediated By Perceived Customer Value - Surya Ardana; Wahju Wulandari; Alfiana (Journal of Management Research and Studies, 2024)
This research aims to determine the influence of digital e-service quality and e-promotion on purchase intentions which are mediated by perceived customer value. The population in this study were feb students at Widyagama University, Malang. A sample of 97 respondents was taken using a non-probability sampling method with purposive sampling technique. Data collection was carried out through distributing questionnaires. Data analysis used SmartPLS Version 3 software. The results of this research show that: 1) E-Service Quality has a positive and significant effect on Purchase Intentions; 2) E-Promotion has a positive and significant effect on Purchase Intention; 3) E-Service Quality has a positive and significant effect on Perceived Customer Value; 4) E- Promotion has a positive and significant effect on Perceived Customer Value; 5) Perceived Customer Value has a positive and significant effect on Purchase Intentions; 6) Perceived Customer Value is able to mediate the relationship between E-Service Quality and Purchase Intentions; and 7) Perceived Customer Value is able to mediate the relationship between E-Promotion and Purchase Intention.